Devices for measurement of the NO2 concentration in the air by means of surface acoustic waves - URBAŃCZYK, M.; JAKUBIK, W.; ADAMCZYK, E.; RZESZOTARSKA, J. (Archives of Acoustics, 1997)
The development of techniques concerning macromolecular compounds have made it possible to get thin layers which change their physico-chemical properties in result of their interaction with the ambient atmosphere. Changes of the physical properties of specially prepared chemically sensitive layers influence the conditions of the propagation of an acoustic surface wave arranged in the layered system piezoelectric waveguide - layer of the compound. Particularly, if the mass and electric conductivity of the chemically sensitive layer is changed, the velocity of the propagation of the acoustic wave changes too.The presented paper include a short review of the SAW gas sensor field and some experimental results for detection a low concentration of NO2 in air.